2022
DOI: 10.1155/2022/5993459
|View full text |Cite|
|
Sign up to set email alerts
|

Metoprolol Mitigates Ischemic Heart Remodeling and Fibrosis by Increasing the Expression of AKAP5 in Ischemic Heart

Abstract: The harm of heart failure mainly causes patients to develop dyspnea, fatigue, fluid retention, and other symptoms, which impair patients’ activity tolerance and lead to a dramatic decrease in patients’ quality of life. The purpose of this study was to verify whether metoprolol regulates AKAP5 expression and test the role of AKAP5 postinjury in mitigating cardiac infarction-associated tissue remodeling and fibrosis. Sprague-Dawley (SD) rats underwent coronary artery ligation (CAL), which was followed immediatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…FOXM1 also drives TGF-β-induced endothelial to mesenchymal transition and, in cardiac endothelial cells, cooperates with the Brahma-related gene-1 ( Brg1 ) chromatin remodeler to trigger the angiotensin-converting enzymes pathological switch leading to angiotensin I-to-II conversion and cardiac hypertrophy [ 45 , 46 ]. Additionally, various studies report a cardioprotective role for A-kinase anchoring protein 5 ( Akap5 ) by regulating calcineurin, calcium/calmodulin-dependent protein kinase II, and β-adrenergic receptors in the heart [ [47] , [48] , [49] ]. Targeting the Hippo pathway, Foxm1 , and Akap5 has tremendous potential as a therapeutic strategy for cardiac fibrosis and hypertrophy, with implications for cardiovascular diseases like CRS.…”
Section: Discussionmentioning
confidence: 99%
“…FOXM1 also drives TGF-β-induced endothelial to mesenchymal transition and, in cardiac endothelial cells, cooperates with the Brahma-related gene-1 ( Brg1 ) chromatin remodeler to trigger the angiotensin-converting enzymes pathological switch leading to angiotensin I-to-II conversion and cardiac hypertrophy [ 45 , 46 ]. Additionally, various studies report a cardioprotective role for A-kinase anchoring protein 5 ( Akap5 ) by regulating calcineurin, calcium/calmodulin-dependent protein kinase II, and β-adrenergic receptors in the heart [ [47] , [48] , [49] ]. Targeting the Hippo pathway, Foxm1 , and Akap5 has tremendous potential as a therapeutic strategy for cardiac fibrosis and hypertrophy, with implications for cardiovascular diseases like CRS.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, previous study found that Akap5knockout mice have significant cardiac hypertrophy, and carvedilol can reverse cardiac hypertrophy and cardiac insufficiency in Akap5 gene knockout mice by regulating the activity of CaN and CaMKII [28,233]. It is worth noting that recent studies have found that Selective β1adrenergic receptor blocker metoprolol reduces ischemic cardiac remodeling and fibrosis by improving cardiac AKAP5 expression and AKAP5-PP2B interaction [234]. Studies have shown that chronic activation of CaN is associated with cardiac hypertrophy and a secondary enhancement of intracellular Ca 2+ treatment that is tied to the hypertrophy response itself, while targeted inhibition of CaN alleviates cardiac hypertrophy in vivo [235][236][237][238][239].…”
Section: Cardiovascular Disordersmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%